Targeted detection of mammalian species using carrion fly‐derived DNA. (4th August 2014) - Schubert, Grit; Stockhausen, Melanie; Hoffmann, Constanze; Merkel, Kevin; Vigilant, Linda; Leendertz, Fabian H.; Calvignac‐Spencer, Sébastien
Abstract DNA analysis from carrion flies (iDNA analysis) has recently been promoted as a powerful tool for cost‐ and time‐efficient monitoring of wildlife. While originally applied to identify any mammalian species present in an area, it should also allow for targeted detection of species and individuals. Using carrion flies captured in the Taï National Park, Côte d'Ivoire, we assessed this possibility by (i) screening carrion fly DNA extracts with nonspecific and species‐specific PCR systems, respectively, targeting mitochondrial DNA (mtDNA) fragments of any mammal or of Jentink's duiker (Cephalophus jentinki), three colobine monkeys (subfamily Colobinae) and sooty mangabey (Cercocebus atys); and (ii) genotyping carrion fly extracts containing sooty mangabey mtDNA. In comparison with the nonspecific PCR assay, the use of specific PCRs increased the frequency of detection of target species up to threefold. Detection rates partially reflected relative abundances of target species in the area. Amplification of seven microsatellite loci from carrion flies positive for sooty mangabey mtDNA yielded an average PCR success of 46%, showing that the identification of individuals is, to some extent, possible. Regression analysis of microsatellite PCR success and mtDNA concentration revealed that, among all carrion flies analysed for this study, 1% contained amounts of mammal mtDNA sufficient to attempt genotyping with potentially high success. We conclude that carrion fly‐derived DNA analysis represents a promising tool for targeted monitoring of mammals in their natural habitat.